The Synergy of a scientific-professional repository and a participative encyclopedia: How to increase the reliability of Wikipedia articles with the contents from Hrčak repository? How to increase the popularity of Hrčak repository with the contents from Wikipedia? (PUBMET, 2023)
Hrčak is the portal of Croatian scientific and professional journals that provides free access to approximately 277,000 papers published in almost 536 journals at the end of April 2023 (https://hrcak.srce.hr). Croatian Wikipedia provides free access to approximately 214,000 articles (hr.wikipedia.org). The advantage of Wikipedia compared to Hrčak is that this online encyclopedia is well known to ordinary Internet users (Singer et al., 2017). The advantage of Hrčak compared to Wikipedia is that information from papers found at Hrčak are generally more reliable than information from Wikipedia articles. For example, the study of Faletar Tanacković et al. has shown that Croatian 'teachers themselves rarely use Wikipedia for academic purposes' (2015). Unreliability of its information is certainly an important reason for that.The goal of the workshop is to point out the possibility of using the mutual advantages of Hrčak and Wikipedia in order to increase the reliability and the extent of information on Wikipedia and to popularize Hrčak portal, its journals and papers. Also, the goal of the workshop is to familiarize the participants with concrete procedures for improving these portals by upgrading and integrating their content: the participants of the workshop will find content for Wikipedia articles in Hrčak and will prepare and add selected content from Hrčak to Wikipedia articles to which they will add citations and we link to Hrčak papers which will be used to increase the reliability of Wikipedia articles.For example, Hrčak has over 100 scientific papers in English that are thematically related to the Croatian city of Šibenik. Based on the selected scientific papers from Hrčak, the workshop participants can update the article about Šibenik on Wikipedia and add references leading to scientific articles on Hrčak. Through various activities that are necessary to expand the Wikipedia article about Šibenik, the participants could gain a range of valuable insights. Among these activities are: (1) reading and analysis of the content of the selected article from Hrčak, (2) selection and adaptation of parts of the text that will be added from the selected Hrčak article about Šibenik to the article about Šibenik on Wikipedia, (3) reading and analysis of the article about Šibenik on Wikipedia in order to determine in which places it can be supplemented with data from the selected article from Hrčak, (4) integration of content from the article on Hrčak into the article about Šibenik on Wikipedia with the principle of fitting the added content as meaningfully as possible into the article on Wikipedia, and finally - (5) adding references in the Wikipedia article to the article on Hrčak with the aim of making interested Wikipedia readers aware of the Hrčak repository, with the aim of informing them that on Hrčak they can found various open access scientific articles about Šibenik and other topics, and with the aim of encouraging the Wikipedia readers to further explore the rich archive of Hrčak.
Keywords: free access; Hrčak; increasing the reliability of information; popularization of science; scientific and professional journals; Wikipedia